Cellulose-based embolism microsphere, preparation method thereof and drug-loaded embolism microsphere

By polymerizing modified cellulose with propylene oxide crosslinking agent, cellulose-based microspheres with ionic functional groups are formed, which solves the problems of insufficient suspension, mechanical properties and drug-carrying properties of existing microspheres, and achieves better drug delivery effects.

CN119701065APending Publication Date: 2025-03-28CARDIOLINK SCI (SHENZHEN) MEDICAL TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411885514.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing cellulose-based embolizing microspheres have poor suspension, insufficient mechanical properties and low drug-carrying performance, which limit their application in drug delivery.

Method used

By polymerizing modified cellulose with a crosslinking agent with a terminal group of propylene oxide, cellulose-based microspheres with ionic functional groups are formed, and their suspension performance, mechanical properties and drug-carrying properties are improved.

Benefits of technology

Modified cellulose-based microspheres have good suspension and mechanical properties in the catheter, and can payload various types of drugs, improving the application scenarios of tumor treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701065A_ABST
    Figure CN119701065A_ABST
Patent Text Reader

Abstract

The invention relates to a cellulose-based embolism microsphere, a preparation method thereof and a drug-loaded embolism microsphere, and belongs to the technical field of medical instruments. The cellulose-based embolism microsphere is prepared by polymerizing modified cellulose and a cross-linking agent of which the end group is epoxypropane group, the modified cellulose includes ionic functional groups including a cationic functional group and an anionic functional group. The cellulose-based embolism microsphere provided by the invention has good suspension property and is more beneficial to passing of a catheter of the microsphere, and the microsphere can load various types of drug molecules by introducing an ionic functional group, so that the application scene of the treatment field is enriched.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of medical device technology, and in particular to a cellulose-based embolic microsphere and a preparation method thereof, and a drug-loaded embolic microsphere. Background Art

[0002] In recent years, intravascular interventional treatment of tumors, especially transcatheter arterial chemotherapy and embolization (TACE), has received extensive attention in the treatment of hepatocellular carcinoma (HCC). Among them, drug-eluting beads (DEB) release chemotherapy drugs in the tumor supply artery through microsphere carriers, showing superior controllable pharmacokinetic properties. Compared with traditional transcatheter arterial chemoembolization (c-TACE), DEB-TACE can effectively reduce the risk of systemic drug release, while improving the safety and tolerability of treatment.

[0003] Microsphere embolic agents have become a research hotspot due to their strong targeting, good therapeutic effect, simple operation and high safety. They selectively embolize the blood vessels supplying the tumor, so that the therapeutic dose is more concentrated in the tumor tissue, directly inducing hypoxic necrosis and reducing damage to normal tissues. In addition, the operation process of microspheres is relatively simple and suitable for local anesthesia, reducing the risks and complications brought by general anesthesia and surgical resection; the wide applicability of microspheres also provides the possibility for the treatment of a variety of malignant tumors.

[0004] Most of the existing cellulose-based embolic microspheres are prepared from unmodified cellulose. The embolic microspheres prepared from unmodified cellulose have high mechanical properties, but poor suspension and low drug loading performance, which limits their application in drug delivery. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing a cellulose-based embolic microsphere and a preparation method thereof, and a drug-loaded embolic microsphere, so as to improve the suspension performance, mechanical properties and drug-loading performance of the embolic microsphere.

[0006] The embodiment of the present application is implemented as follows:

[0007] In a first aspect, an embodiment of the present application provides a cellulose-based embolic microsphere, comprising: a modified cellulose polymerized with a cross-linking agent having a terminal propylene oxide group; the modified cellulose comprises an ionic functional group, and the ionic functional group comprises a cationic functional group and an anionic functional group.

[0008] In the above technical scheme, firstly, the cellulose-based embolic microspheres are polymerized by modified cellulose and a cross-linking agent with an end group of propylene oxide. This cross-linking structure not only enhances the mechanical strength and stability of the microspheres, but also gives them good elasticity and toughness, so that the microspheres can withstand the flow and pressure changes in the blood vessels during use without being easily broken; secondly, the density of the microspheres is improved, so that the microspheres have good suspension properties, can be transported in the catheter without damage, and can meet the needs of complex intervention situations such as catheter bending; finally, the ionic functional groups introduced into the modified cellulose, including cationic functional groups and anionic functional groups, not only improve the hydrophilicity of the microspheres, but also enhance their interaction with drug molecules and improve the drug loading capacity of the drug. At the same time, it can load multiple types of drugs and enhance the application scenarios in the field of tumor treatment. Specifically, the cationic functional groups can effectively bind to negatively charged drug molecules, while the anionic functional groups can interact with positively charged drug molecules. This diverse binding ability enables the microspheres to load multiple types of drugs.

[0009] In the second aspect, an embodiment of the present application provides a method for preparing the above-mentioned cellulose-based embolic microspheres, comprising: S1. dissolving an alkaline catalyst in water, adding a cellulose compound to form a cellulose aqueous solution, and then sequentially adding a modifier and a cross-linking agent to obtain an aqueous solution; S2. adding the aqueous solution to an oil-phase solution containing a dispersant under stirring to obtain an oil-in-water reverse suspension polymerization system; S3. maintaining the stirring state, and sequentially heating, reacting, purifying and collecting the oil-in-water reverse suspension polymerization system to obtain cellulose-based embolic microspheres.

[0010] In the above technical scheme, the present application uses cellulose compounds as raw materials, introduces ionic functional groups on cellulose compounds through modifiers, and then uses glycidyl ethers with propylene oxide at the end as crosslinking agents to form cellulose-based microspheres through epoxy ring-opening crosslinking polymerization; the present application uses a preparation method of first introducing positive and negative charge groups and then crosslinking. The first introduction of positive and negative charges can fully graft positive and negative charge groups on cellulose, fully grafting positive and negative charge groups to achieve a high-density group grafting rate of cellulose, and then achieve a crosslinking reaction. The grafting of high-density functional groups on cellulose gives the microspheres high-density charges, thereby enhancing the comprehensive mechanical properties of the microspheres, and the ionically modified cellulose-based microspheres have good suspension properties and have a variety of drug loading properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1 The results of the drug loading rate determination of doxorubicin hydrochloride loaded on the embolic microspheres prepared in Examples 1-4 of the present application;

[0013] Figure 2 The results of drug loading rate determination of diclofenac sodium hydrochloride loaded on the embolic microspheres prepared in Examples 1-4 of the present application;

[0014] Figure 3 The results of drug loading rate determination of raltitrexine loaded on the embolic microspheres prepared in Examples 1-4 of the present application;

[0015] Figure 4 These are the results of drug loading rate determination of siRNA loaded on the embolic microspheres prepared in Examples 1-4 of the present application. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0017] The following is a detailed description of a cellulose-based embolic microsphere and a preparation method thereof, and a drug-loaded embolic microsphere according to an embodiment of the present application.

[0018] The embodiment of the present application provides a cellulose-based embolic microsphere, comprising: a modified cellulose and a cross-linking agent having a terminal propylene oxide group polymerized; the modified cellulose includes an ionic functional group, and the ionic functional group includes a cationic functional group and an anionic functional group.

[0019] Among them, the crosslinking agent includes a glycidyl ether compound with a terminal group of propylene oxide. As an example, the glycidyl ether compound includes but is not limited to glycerol diglycidyl ether, polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, glycerol triglycidyl ether, resorcinol diglycidyl ether, bisphenol A diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, PEG 500 - one or more of diglycidyl ether and pentaerythritol glycidyl ether.

[0020] The structure of the cross-linking agent can achieve different dense structures of the microspheres, regulate the mechanical properties of the microspheres, and the density (suspension performance). At the same time, the chain spacing in the microspheres with different cross-linking degrees will lead to the neutralization degree of the positive and negative groups, thereby affecting the drug loading. Therefore, the present application can obtain higher mechanical strength, higher elasticity and appropriate density by selecting the above-mentioned types of cross-linking agents, which enables the microspheres to be transported in the catheter without damage while having good suspension properties, and can meet the needs of complex intervention situations such as catheter bending.

[0021] The ionic functional groups of the modified cellulose are obtained by bonding the functional groups of the modifier and the hydroxyl groups on the cellulose compound.

[0022] Introducing ionic functional groups on cellulose compounds can increase the charge density of microspheres, thereby improving the adhesion and loading capacity of drugs, thereby increasing the drug loading of microspheres. Moreover, ionic functional groups usually have good hydrophilicity, which can improve the solubility and biocompatibility of modified cellulose. On the one hand, it makes the microspheres have better suspension performance in the physiological environment and enhances the permeability of the catheter; on the other hand, it has good mechanical properties. The cationic functional groups in the ionic functional groups combine with anionic drugs, and the anionic functional groups are suitable for combining with cationic drugs to achieve the loading of different types of drugs, enriching the loading types of drugs, which allows the microspheres to design suitable drug release curves for different treatment needs.

[0023] In some embodiments of the present application, the cellulose compound includes at least one of cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose.

[0024] In some embodiments of the present application, the modifier includes an anionic modifier and a cationic modifier, wherein the anionic modifier includes a compound with a sulfonic acid group, and the cationic modifier includes glycidyl trimethyl ammonium chloride.

[0025] Anionic modifiers with sulfonic acid groups can form strong electrostatic interactions with cationic drugs, thereby improving the drug loading capacity. This ionic interaction allows the microspheres to effectively adsorb and bind a variety of charged drugs, such as cationic drugs, anionic drugs, and nucleic acid drugs. In addition, the sulfonic acid group can significantly improve the hydrophilicity of the microspheres, making them easier to disperse in a physiological environment, thereby enhancing their biocompatibility. Glycidyl trimethylammonium chloride, as a cationic modifier, increases the surface positive charge of the microspheres and can also bind to anionic drugs to further increase the drug loading and release efficiency. By using anionic and cationic modifiers at the same time, microspheres can achieve multiple functions, such as improving the controllability of drug release and enhancing the drug loading rate of microspheres.

[0026] As an example, the compound having a sulfonic acid group includes, but is not limited to, one or more of 1,4-butane sultone, 1,3-propane sultone and sodium 2-chloroethyl sulfonate.

[0027] The present application sulfonates the polyhydroxy long-chain polymer by using the above-mentioned compounds containing sulfonic acid groups, and introduces sulfonic acid groups by reacting with the hydroxyl groups on cellulose to form ether bonds. The sulfonic acid groups are connected via ether bonds to make the structure more stable, thereby giving the embolic microspheres more stable functional groups.

[0028] The preparation method of the above-mentioned cellulose-based embolic microspheres is described below.

[0029] A method for preparing cellulose-based embolic microspheres comprises the following steps:

[0030] (1) Preparation of aqueous solution

[0031] The alkaline catalyst is dissolved in water, and a cellulose compound is added to form a cellulose aqueous solution, and then a modifier and a cross-linking agent are added in sequence, and stirred for 1-120 minutes to obtain an aqueous phase solution.

[0032] In the above alkaline aqueous solution, the mass concentration of the alkaline catalyst is 10-30%. By way of example, the mass concentration of the added alkaline catalyst includes but is not limited to 10%, 13%, 15%, 20%, 22%, 24%, 26%, 28%, and 30%.

[0033] A higher alkaline catalyst concentration (such as 10-30%) can effectively increase the solubility of cellulose. Alkaline conditions help to destroy the hydrogen bonds of cellulose, making it easier to dissolve in water and forming a uniform cellulose aqueous solution. Within this alkaline catalyst concentration range, it helps the cross-linking reaction to form a dense cross-linked structure, thereby enhancing the mechanical strength of the microspheres; it can also enhance the collision frequency between the reactants, thereby accelerating the reaction between the modifier and cellulose, shortening the reaction time, and improving production efficiency. In addition, within the above alkaline catalyst concentration range, it can promote the reaction between the modifier and the cellulose hydroxyl group, so that the number of generated ionic functional groups is sufficient, thereby improving the drug loading capacity and hydrophilicity of the microspheres.

[0034] In some embodiments of the present application, the alkaline catalyst includes KOH and / or NaOH. In some embodiments of the present application, under stirring conditions, the alkaline catalyst is first added to water to prepare an alkaline aqueous solution, and the cellulose compound is added to the alkaline aqueous solution to dissolve to form a cellulose aqueous solution; then a modifier is added, and the reaction is carried out at 30-100° C. for 1-5 hours to obtain a modified cellulose solution; then a cross-linking agent is added to the modified cellulose solution, and the mixture is stirred for 1-120 minutes to obtain an aqueous phase solution.

[0035] Firstly dissolving the alkaline catalyst in water can make the alkaline catalyst evenly dispersed in the water phase, thereby improving its dissolution effect on cellulose. This uniformity helps to form a stable cellulose aqueous solution. Carrying out the reaction of the modifier in the temperature range of 30-100°C can accelerate the modification process of cellulose. After obtaining the modified cellulose solution, adding a crosslinking agent and stirring can effectively control the crosslinking reaction. The flexible choice of stirring time (1-120min) makes the production process more controllable, can adjust the particle size and morphology of the microspheres, and improve the uniformity and stability of the final product.

[0036] Among them, the mass percentage of cellulose compounds is 1-6%. As an example, the mass percentage of cellulose compounds includes but is not limited to 1%, 1.3%, 1.5%, 1.8%, 2%, 2.4%, 2.7%, 3%, 3.2%, 3.5%, 3.9%, 4.1%, 4.5%, 5%, 5.3%, 5.7%, and 6%.

[0037] Selecting a 1-6% concentration of the cellulose compound can improve its good solubility in alkaline aqueous solution, which helps to improve the reaction efficiency between cellulose and the modifier. Moreover, the cellulose compound within this concentration range can effectively adjust the particle size and morphology of the final microspheres. For example, a lower concentration helps to form smaller microspheres, while a moderate concentration can generate larger and more stable microspheres. It can be selected and optimized according to actual needs.

[0038] In the above-mentioned aqueous phase solution, the mass ratio of the crosslinking agent to the cellulose compound is (0.025-0.15):1. By way of example, the mass ratio of the crosslinking agent to the cellulose compound includes but is not limited to 0.025:1, 0.035:1, 0.045:1, 0.05:1, 0.055:1, 0.06:1, 0.075:1, 0.085:1, 0.095:1, 0.1:1, 0.12:1, and 0.15:1.

[0039] The mass ratio of the crosslinking agent to the cellulose compound is limited to (0.025-0.15):1. This ratio range can achieve a moderate crosslinking reaction and improve the mechanical strength and stability of the microspheres. The mass ratio of the crosslinking agent to the cellulose is within the above range, which can better regulate the particle size, morphology and porosity of the microspheres and adjust the physical properties of the microspheres, so that they can meet the specific requirements for particle size and pore structure in different applications. Moreover, the pore structure of the microspheres formed by the crosslinking reaction carried out within the above ratio range can effectively accommodate more drug molecules, thereby improving the drug loading rate.

[0040] In the above-mentioned aqueous phase solution, the mass ratio of the modifier to the cellulose compound is (0.05-0.5):1. By way of example, the mass ratio of the modifier to the cellulose compound includes but is not limited to 0.05:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, 0.23:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.42:1, 0.45:1, 0.48:1, and 0.5:1.

[0041] The mass ratio of the modifier to the cellulose compound is limited to (0.05-0.5):1. This ratio range enables an effective reaction between the modifier and the cellulose compound, and improves the hydrophilicity of the microspheres and the drug loading capacity.

[0042] (2) Preparation of oil phase solution

[0043] Under stirring, an oil-soluble dispersant is added to the oil phase solvent to obtain an oil phase solution.

[0044] Wherein, the dispersant includes Tween series compounds and / or Span series compounds, such as Tween 20 and Span 80. As an example, the mass ratio of Tween 20 to Span 80 is 1:(1-5). The mass ratio of Tween 20 to Span 80 includes but is not limited to 1:1, 1:2, 1:3, 1:4, and 1:5.

[0045] The oil phase solvent includes but is not limited to at least one of liquid paraffin, n-heptane, ethyl acetate and butyl acetate.

[0046] In some embodiments of the present application, the mass percentage of the dispersant in the oil phase solution is 0.5-5%. As an example, the mass percentage of the dispersant in the oil phase solution includes but is not limited to 0.5%, 0.7%, 1%, 0.5%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 2.7%, 3%, 3.4%, 3.8%, 4%, 4.3%, 4.5%, 4.7%, 5%.

[0047] (3) Inverse suspension polymerization

[0048] Under the condition of stirring rate of 100-500r / min, the aqueous phase solution in step (1) is slowly dripped into the oil phase solution in step (2) to form an oil-in-water reverse suspension polymerization system. After the dripping is completed, the reverse suspension polymerization system is heated to 30-90°C, kept in heating and stirring state, and heated reaction is carried out, and the reaction time is 5-36h.

[0049] A stable microsphere structure can be formed through inverse suspension polymerization. By controlling the stirring rate to 100-500r / min, the particle size and morphology of the microspheres can be effectively adjusted to meet the needs of different applications. Reacting the inverse suspension polymerization system at 30-90°C for 5-36h can enhance the cross-linking reaction and form more stable microspheres.

[0050] (4) Microsphere purification and collection

[0051] After the reaction is completed, stirring and heating are stopped, the layers are allowed to stand, the oil phase is separated, the microspheres are collected, and the microspheres are washed with petroleum ether, butyl acetate, sodium bicarbonate aqueous solution and ultrapure water in turn. After sieving, polyhydroxy long-chain polymer embolic microspheres with different particle size distributions are obtained.

[0052] Among them, static stratification can effectively separate the oil phase and the water phase, so as to enable efficient collection of the microspheres; then by using petroleum ether, butyl acetate, sodium bicarbonate aqueous solution and ultrapure water to wash the microspheres in sequence, the unreacted raw materials, residual modifiers and cross-linking agents can be removed to improve the purity of the microspheres; the screening step can effectively separate microspheres of different particle sizes to meet various application requirements.

[0053] The embodiment of the present application also provides a drug-loaded embolic microsphere, comprising any of the above-mentioned cellulose-based embolic microspheres, and also comprising a drug loaded in the cellulose-based embolic microspheres, wherein the drug comprises at least one of a cationic drug doxorubicin hydrochloride, an anionic drug diclofenac sodium hydrochloride, a zwitterionic compound raltitrexed, and a nucleic acid drug siRNA.

[0054] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0055] Example 1

[0056] This embodiment provides a cellulose-based embolic microsphere, which can be prepared by the following synthetic route:

[0057]

[0058] The preparation method comprises the following steps:

[0059] (1) Preparation of aqueous solution

[0060] Under stirring conditions, a 25 wt % NaOH solution is prepared, hydroxyethyl cellulose is dissolved in the NaOH solution, 1,4-butanesulfonate and glycidyl trimethylammonium chloride are subsequently added, and glycerol triglycidyl ether is finally added, and the mixture is stirred for 1 hour to obtain an aqueous phase solution; the mass fraction of hydroxyethyl cellulose in the aqueous phase solution is 6%, and the molar ratio of hydroxyethyl cellulose to glycidyl trimethylammonium chloride is 1:1, the molar ratio of hydroxyethyl cellulose to 1,4-butanesulfonate is 1:1, and the molar ratio of hydroxyethyl cellulose to glycerol triglycidyl ether is 10:1.

[0061] (2) Preparation of oil phase solution

[0062] Under stirring, Tween 20 and Span 80 were added to liquid paraffin in a mass ratio of 1:3 (mass percentage of the dispersant was 3%) to obtain an oil phase solution.

[0063] (3) Inverse suspension polymerization

[0064] Under the condition of stirring rate of 300r / min, the aqueous solution in step (1) is slowly dripped into the oil phase solution in step (2) to form an oil-in-water reverse suspension polymerization system; wherein, after the dripping is completed, the reverse suspension polymerization system is heated to 80°C and maintained in a heating and stirring state to carry out a heating reaction, and the stirring and heating are stopped after the reaction for 16 hours.

[0065] (4) Microsphere purification and collection

[0066] After the reaction is completed, stirring and heating are stopped, the layers are allowed to stand, the oil phase is separated, the microspheres are collected, and the microspheres are washed with petroleum ether, butyl acetate, sodium bicarbonate aqueous solution and ultrapure water in sequence. After screening, cellulose-based embolic microspheres with different particle size distributions are obtained.

[0067] Example 2

[0068] This embodiment provides a cellulose-based embolic microsphere, which can be prepared by the following synthetic route:

[0069]

[0070] The preparation method comprises the following steps:

[0071] (1) Preparation of aqueous solution

[0072] Under stirring conditions, a 25wt% NaOH solution is prepared, hydroxyethyl cellulose is dissolved in the NaOH solution, 1,4-butanesulfonate and glycidyl trimethylammonium chloride are subsequently added, and polyethylene glycol diglycidyl ether is finally added, and stirred for 1 hour to obtain an aqueous phase solution; the mass fraction of hydroxyethyl cellulose in the aqueous phase solution is 6%, and the feeding molar ratio of hydroxyethyl cellulose to glycidyl trimethylammonium chloride is 1:1, the feeding molar ratio of hydroxyethyl cellulose to 1,4-butanesulfonate is 1:1, and the feeding molar ratio of hydroxyethyl cellulose to polyethylene glycol diglycidyl ether is 10:1.

[0073] The remaining steps (2), (3) and (4) are the same as those in Example 1.

[0074] Example 3

[0075] This embodiment provides a cellulose-based embolic microsphere, which can be prepared by the following synthetic route:

[0076]

[0077] The preparation method comprises the following steps:

[0078] (1) Preparation of aqueous solution

[0079] Under stirring conditions, a 25wt% NaOH solution is prepared, hydroxyethyl cellulose is dissolved in the NaOH solution, then 1,4-butanesulfonate and glycidyl trimethylammonium chloride are added, and finally pentaerythritol glycidyl ether is added, and stirred for 1 hour to obtain an aqueous phase solution; the mass fraction of hydroxyethyl cellulose in the aqueous phase solution is 6%, and the feeding molar ratio of hydroxyethyl cellulose to glycidyl trimethylammonium chloride is 1:1, the feeding molar ratio of hydroxyethyl cellulose to 1,4-butanesulfonate is 1:1, and the feeding molar ratio of hydroxyethyl cellulose to pentaerythritol glycidyl ether is 10:1.

[0080] The remaining steps (2), (3) and (4) are the same as those in Example 1.

[0081] Example 4

[0082] This embodiment provides a cellulose-based embolic microsphere, which can be prepared by the following synthetic route:

[0083]

[0084] The preparation method comprises the following steps:

[0085] (1) Preparation of aqueous solution

[0086] Under stirring conditions, prepare a 25wt% NaOH solution, dissolve hydroxyethyl cellulose in the NaOH solution, then add 1,4-butanesulfonic acid lactone and glycidyl trimethylammonium chloride, and finally add PEG 500 - diglycidyl ether, stirred for 1 hour to obtain an aqueous phase solution; the mass fraction of hydroxyethyl cellulose in the aqueous phase solution is 6%, and the feeding molar ratio of hydroxyethyl cellulose to glycidyl trimethyl ammonium chloride is 1:1, the feeding molar ratio of hydroxyethyl cellulose to 1,4-butanesulfonate is 1:1, and the feeding molar ratio of hydroxyethyl cellulose to PEG is 1:1. 500 -The feeding molar ratio of diglycidyl ether is 10:1.

[0087] The remaining steps (2), (3) and (4) are the same as those in Example 1.

[0088] Test Example 1

[0089] In this test example, the cellulose-based embolic microspheres prepared in Examples 1-4 were tested for physical properties, including strength, elasticity and density.

[0090] The elasticity determination method is as follows: take the cellulose-based embolic microspheres prepared in Examples 1-6 and Comparative Example 1, spread them on a glass slide, place them under the probe of a texture analyzer (TA XT plusC), and select the Hold Compression mode for testing.

[0091] The density test method is: measure 1 mL of the cellulose-based embolic microspheres prepared in Examples 1-4 and weigh the mass. The ratio of the mass to the volume is the density of the microspheres.

[0092] Please see Table 1 for the above performance test results.

[0093] Table 1

[0094] Microspheres Strength / g elasticity(%) Density(g / mL) Example 1 257.8 38.1 1.15 Example 2 243.7 46.5 1.13 Example 3 273.4 17.9 1.19 Example 4 229.4 57.3 1.09

[0095] As shown in Table 1, the embolic microspheres in Example 3 have the highest strength and density, and the lowest elasticity, indicating that the embolic microspheres are relatively dense. This is because the higher the functionality of the cross-linking agent, the higher the strength of the obtained embolic microspheres, but the elasticity is correspondingly reduced. The embolic microspheres in Example 4 have the highest elasticity and lower strength. This is because at the same functionality, the longer the carbon chain of the cross-linking agent, the lower the strength and density of the obtained embolic microspheres, but the elasticity is increased.

[0096] In summary, the cellulose-based embolic microspheres in the embodiments of the present application can obtain higher mechanical strength, higher elasticity and appropriate density by changing the type of cross-linking agent, which enables the embolic microspheres to have good suspension properties while being able to be transported in the catheter without damage, and can meet the needs of complex interventional situations such as catheter bending.

[0097] Test Example 2

[0098] In this test example, the drug loading performance of the embolic microspheres prepared in Examples 1-4 was tested respectively, and the drugs used included the cationic drug doxorubicin hydrochloride, the anionic drug diclofenac sodium hydrochloride, the zwitterionic compound raltitrexed, and the nucleic acid drug siRNA.

[0099] Test method: The embolic microspheres prepared in Examples 1-4 were taken into three groups (each group was 1 mL) and numbered, and the surface moisture of the embolic microspheres was removed by filter paper. The embolic microspheres were transferred into a vial, and 5 mL of a cationic drug doxorubicin hydrochloride solution (20 mg / mL), an anionic drug diclofenac sodium hydrochloride solution (20 mg / mL), a zwitterionic compound raltitrexed solution (20 mg / mL), and a nucleic acid drug siRNA solution (2 mg / mL) were added, respectively. The mixture was mixed and shaken, and the solution concentration was tested at 5 min, 30 min, and 60 min, respectively. The drug loading rate of the embolic microspheres was calculated, and the drug loading curves of each drug corresponding to Examples 1-4 were drawn.

[0100] Please see Table 2 for the above results of drug loading rate of embolic microspheres.

[0101] Table 2

[0102]

[0103] Figure 1 The results of the drug loading rate determination of doxorubicin hydrochloride loaded on the embolic microspheres prepared in Examples 1-4 of the present application; Figure 2 The results of drug loading rate determination of diclofenac sodium hydrochloride loaded on the embolic microspheres prepared in Examples 1-4 of the present application; Figure 3 The results of drug loading rate determination of raltitrexine loaded on the embolic microspheres prepared in Examples 1-4 of the present application; Figure 4 These are the results of drug loading rate determination of siRNA loaded on the embolic microspheres prepared in Examples 1-4 of the present application.

[0104] From Table 2 and Figure 1-Figure 4It can be seen that after double ion modification, the cellulose-based embolic microspheres have good loading capacity for cationic drugs, anionic drugs and nucleic acid drugs. The cross-linking degree of the embolic microspheres in Example 1 and Example 2 is moderate. On the one hand, there is a certain distance between the positive and negative charge groups, resulting in the positive and negative charges not being neutralized with each other, so that more drugs can be loaded and the drug loading is high; on the other hand, the moderate cross-linking degree causes the gaps in the microsphere network structure to not be too small or too large, and has good mechanical properties. It also has a suitable density, giving the microspheres good suspension and catheter permeability. The microspheres in Example 3 are the most dense, with smaller pores, which limits the exchange of drugs; in addition, the smaller chain spacing will cause the positive and negative charges on the cellulose chains to neutralize each other, resulting in a decrease in charge density. These two points lead to poor drug loading performance. The microspheres in Example 4 have the largest pores, which are conducive to drug flow while avoiding charge neutralization between cellulose chains, so the drug loading is high, but the ball is soft as a whole, and the comprehensive mechanical properties are relatively poor.

[0105] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A cellulose-based embolic microsphere, characterized in that: include: It is formed by polymerizing modified cellulose and a cross-linking agent with a terminal propylene oxide group; The modified cellulose includes ionic functional groups, and the ionic functional groups include cationic functional groups and anionic functional groups.

2. The cellulose-based embolic microspheres according to claim 1, characterized in that: The cross-linking agent includes a glycidyl ether compound having an end group of propylene oxide; Optionally, the glycidyl ether compound includes glycerol diglycidyl ether, polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, glycerol triglycidyl ether, resorcinol diglycidyl ether, bisphenol A diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, PEG 500 - one or more of diglycidyl ether and pentaerythritol glycidyl ether.

3. The cellulose-based embolic microspheres according to claim 1, characterized in that: The ionic functional groups of the modified cellulose are obtained by bonding the functional groups of the modifier and the hydroxyl groups on the cellulose compound; Optionally, the modifier includes an anionic modifier and a cationic modifier; Optionally, the anionic modifier comprises a compound with a sulfonic acid group, and the cationic modifier comprises glycidyl trimethyl ammonium chloride; Optionally, the cellulose compound includes at least one of cellulose, hydroxymethyl cellulose and hydroxyethyl cellulose.

4. The cellulose-based embolic microspheres according to claim 3, characterized in that: The compound with a sulfonic acid group includes one or more of 1,4-butane sultone, 1,3-propane sultone and sodium 2-chloroethyl sulfonate.

5. A method for preparing cellulose-based embolic microspheres according to any one of claims 1 to 4, characterized in that: include: S1. dissolving an alkaline catalyst in water, adding a cellulose compound to form an aqueous cellulose solution, and then sequentially adding a modifier and a cross-linking agent to obtain an aqueous solution; S2. Under stirring, the aqueous solution is added to the oil phase solution containing a dispersant to obtain an oil-in-water reverse suspension polymerization system; S3. Maintaining the stirring state, the water-in-oil reverse suspension polymerization system is subjected to heating reaction, purification and collection in sequence to obtain the cellulose-based embolic microspheres.

6. The preparation method according to claim 5, characterized in that: In the aqueous phase solution, the mass percentage of the cellulose compound is 1-6%; and / or, the cross-linking agent accounts for 2.5 to 15% by mass of the cellulose compound; And / or, the mass percentage of the modifier to the cellulose compound is 5-50%.

7. The preparation method according to claim 5, characterized in that: In step S1, after adding the modifier to the cellulose aqueous solution, heating reaction is carried out for a period of time, and then the cross-linking agent is added; Optionally, the conditions for the heating reaction include: a heating temperature of 30-100° C. and a reaction time of 1-5 h.

8. The preparation method according to claim 5, characterized in that: In step S3, the reverse phase suspension polymerization system is heated to 30-90° C. at a stirring rate of 100-500 r / min to carry out the heating reaction for 5-36 hours.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The alkaline catalyst includes KOH and / or NaOH; Optionally, the mass percentage of the dispersant in the oil phase solution is 0.5-5%; Optionally, the dispersant includes Tween series compounds and / or Span series compounds; Optionally, the dispersant includes Tween 20 and Span 80, and the mass ratio of the Tween 20 to the Span 80 is 1:(1-5).

10. A drug-loaded embolic microsphere, characterized in that: The cellulose-based embolic microspheres according to any one of claims 1 to 4 further include drugs loaded in the cellulose-based embolic microspheres, wherein the drugs include at least one of the cationic drug doxorubicin hydrochloride, the anionic drug diclofenac sodium hydrochloride, the zwitterionic compound raltitrexed and the nucleic acid drug siRNA.